Is U.S. Multinational Dividend Repatriation Policy Influenced by Reporting Incentives? - Blouin, Jennifer L.; Krull, Linda K.; Robinson, Leslie A. (The Accounting Review, 2012)
ABSTRACT This study finds evidence that public-company reporting by U.S. multinational corporations (MNCs) creates disincentives to repatriate foreign earnings to the U.S. and contributes to the accumulation of cash abroad. MNCs operate under U.S. international tax laws and financial reporting rules and face two potential consequences when they repatriate foreign earnings: a cash payment for repatriation taxes and a reduction in reported accounting earnings. Using a confidential dataset of financial and operating characteristics of foreign affiliates of MNCs combined with public-company data, we examine how repatriation amounts vary across firms that face relatively strong reporting incentives to defer an accounting expense. Our results suggest that reporting incentives reduce repatriations by about 17 to 21 percent annually. Data Availability: Bureau of Economic Analysis (BEA) data were made available to the authors under a legal confidentiality arrangement; all non-BEA data are available from public sources.